(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdOjGJs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdOjGJ, hGdfXQ aj CehQ CQHYI(B: (3GdChd aj CbSGe GdbJd hebGOjQ GdOjGJ(B. (3GdbJd YeO hbO Sda eKGdg, hTHg GdYeO eKd Cf jVQH ddJCOjHs
(3BNQgG (B:s
(3BNQgG(B: (3hdh HTLI hGMOI hGNJda ebGOjQgG , CNP OjI GdCHZ cCfgG dh cGfJ cdgG cCf de JQO Ydi OjJgG Cbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis